PENGARUH SERBUK CANGKANG TELUR AYAM DAN PUPUK NPK 16:16:16 TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Roni Setiawan; Saripah Ulpah; Raisa Baharuddin (DINAMIKA PERTANIAN, 2019)
Tomato (Lycopersicum esculentum Mill.) is one of the vegetables that have high economic value. However, tomato production in Riau is constrained by low fertility and acidity. Egg shell waste can be used as a substitute for lime to increase soil pH. NPK fertilizer is used to provide nutrients for plants. This study aims to determine the effect of chicken eggshell powder and NPK 16:16:16 fertilizer on the growth and yield of tomato plants. This research was conducted in the experimental farm of the Faculty of Agriculture, Riau Islamic University, Pekanbaru. The study was conducted from March to July 2019. The study was conducted using a completely randomized design (CRD) with 16 treatments and repeated 3 times. The first factor was chicken eggshell powder with 4 levels (0, 15, 30, 45 g/plant) and the second factor was NPK fertilizer 16:16:16 with 4 levels (0, 10, 20, 30 g/plant). The results showed that the interactions occurred in the number of fruits per plant, fruit weight per plant on reatments for 45 g of chicken eggshell powder/plant and NPK 16:16:16 30 g / plant.